The effects of e‐beam crosslinking of LDPE on the permeation of hydrocarbons. Issue 25 (6th March 2017) - Berger, Katrin; Keimel, Christian; Helfer, Eric; Haar, Bernd; Mattausch, Hannelore; Riess, Gisbert; Kern, Wolfgang
ABSTRACT: Polyethylene is a useful material in numerous applications, such as packaging, fuel tanks as well as oil and gas pipes. However, it must be considered that polyethylene is permeable to gases and liquids. Small molecules, such as hydrocarbons, may permeate through the material and cause environmental problems. Consequently, a particular aspect of polymer materials is the requirement of a high permeation resistance against low‐molecular‐weight hydrocarbons. Modifications of the commonly used polyethylene material are necessary to achieve adjusted permeation properties. In this contribution, the effect of electron‐beam crosslinking of polyethylene on the resulting permeation characteristics was investigated. Polyethylene sheets were processed and crosslinked by irradiation with high energy electrons. The formation of a network structure was characterized by gel content determination and by rheological measurements. The permeation properties of the polymer sheets were assessed by a gravimetric method. It is demonstrated that—as a result of the crosslinking process—the permeation of low molecular weight hydrocarbon through polyethylene is reduced with respect to the chain length of the aliphatic substances. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44968. Abstract :